Research Trends of E-Module Problem Based Learning Model to Improve Creative Thinking Skills of Learners (2016-2025): Literature Review - Wiwin Melia Utari; Agil Al Idrus (Balai Publikasi Indonesia, 2025)
One of the important skills for Indonesian people in the digital era is the ability to think creatively. Creative thinking is an aspect of life skills that must be improved to face the information age and increasingly intense competition. One of the high-level thinking abilities that can be utilised to solve problems in the learning process is student creativity. In problem solving, the application of creative thinking can generate various ideas that are useful for finding solutions. To support active learning, it is very important to have appropriate teaching materials, so that students can understand the material better and achieve learning objectives, one of which is through the use of problem-based learning e-modules. This study aims to identify, analyse the tendency of e-modules of problem-based learning models to improve students' creative thinking skills. This research method is descriptive and analytical. The data used in this study were obtained from documents indexed by google scholar from 2016-2025 using publish or perish and dimension.ai. The data identified and analysed are the type of publication, the source of publication, and the title of the research on the PBL e-module model to improve students' creative thinking skills that are widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results showed an increase in the number of publications from 2016 to 2023, with the peak of publications occurring in 2023. However, there are fluctuations that show the challenges in this study. In addition, there are many types of publications in the form of articles, procceding, chapters, edited books, preprints and monographs. However, the most common type of publication is article, signalling the strong contribution of research in this area